Closing the gender gap: Marta Guadalupe Rivera Ferre - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Marta Guadalupe Rivera Ferre at the Closing the gender gap in farming under climate change event held 19 March 2015 in Paris Read more about the event: https://ccafs.cgiar.org/events/closing-gender-gap-farming-under-climate-change-new-knowledge-renewed-action